Renewable Energy in Sub-Saharan Africa: A Prescriptive Analysis of Ghana - Gyimah, Leo Andoh Adjei; Gyimah, Adjei Gyamfi (Environmental Management and Sustainable Development, 2024)
This study assesses the state of play of renewable energy in Sub-Saharan Africa through the lens of the Ghana renewable energy sub-sector. Adopting a sector diagnostic approach, the study assesses the legal framework, institutional arrangements, emerging developments, and challenges of renewable energy development in Ghana. The study further prescribes key renewable policy instruments necessary to propel Ghana to achieve its 10% renewable energy target by 2030. Recommended amendments for the Renewable Energy Act are also proffered in this paper. The study provides innovative directions for policymakers and regulators while revealing new perspectives to the renewable energy puzzle in Africa.